Pelatihan Pembuatan Ecoenzyme Sebagai Usaha Pengolahan Sampah Rumah Tangga Desa Randuwatang - Nasrulloh, Muhammad Farid; Said, Rahmad; Hidayatulloh, Faisol; Maksum, Mochammad Ja’far Sodiq; Darmawan, Muhammad Faridl (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The Randuwatang Village Government has provided TPS 3R (Integrated Waste Disposal Site Reduce, Reuse, Recycle) to accommodate the large amount of domestic waste that is thrown away and causes pollution. However, there is no drive to process domestic waste. This is a problem that exists in Randuwatang village. Based on the problems above, in community service activities in this community partnership scheme we provide training to the community on how to make Eco Enzyme using basic ingredients from organic kitchen waste such as fruit peels and vegetable scraps. It is hoped that holding this training can reduce waste in Randuwatang village. Making Eco Enzyme is an effective waste management method. The approach method for implementing community service activities in Randuwatang village is using lecture, discussion and training methods. From the percentage of questionnaire results, it can be concluded that there has been an increase in public knowledge regarding Ecoenzymes both in terms of ingredients, how to make and how to use them. Before the socialization was carried out, public knowledge about Ecoenzymes was only 20% and after the socialization was carried out, public knowledge about Ecoenzymes increased by 80%.